Survival of all-ceramic restorations after a minimum follow-up of five years: A systematic review - Araujo, Nara Santos [UNESP]; Moda, Mariana Dias [UNESP]; Silva, Ebele Adaobi [UNESP]; Zavanelli, Adriana Cristina [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Pellizzer, Eduardo Piza [UNESP] (My University, 2016)
Objective: The purpose of this systematic review was to compare the survival and complication rates of all-ceramic restorations after a minimum follow-up time of 5 years. Data Sources: A comprehensive search of studies published from 2005 to November 2015 and listed in the PubMed/MEDLINE, Scopus, and Cochrane Library databases was performed in accordance with the PRISMA statement. Two reviewers independently analyzed the abstracts. Relevant studies were selected according to predetermined inclusion criteria. Results: Twenty-nine studies were selected for the final analysis from an initial yield of 514. Only four studies fulfilled the requirement of having a randomized design, and 25 studies were prospective with a mean follow-up period of 5 to 16 years. Overall, the 5-year complication rates were low. The most frequent complications were secondary caries, endodontic problems, ceramic fractures, ceramic chipping, and loss of retention. Conclusion: This systematic review showed that all-ceramic restorations fabricated using the correct clinical protocol have an adequate clinical survival for at least 5 years of clinical service with very low complication rates. Minor ceramic chipping and debonding did not affect the longevity of the restorations. Clinical Relevance: Long-term clinical performance of all-ceramic restorations manufactured using various ceramic systems provides clinical evidence of complications and long-term management of these restorations. Available evidence indicates the effectiveness of many ceramic systems for numerous clinical applications. Correct planning and a rigorous technical execution protocol increase clinical success. Studies of ceramic prostheses indicate more problems with ceramic failure and debonding.
Keywords: Dental ceramic; Failure; Restorations; Systematic review